2004
DOI: 10.1111/j.1399-0012.2004.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplants from non‐heart beating paracetamol overdose donors

Abstract: Non-heart beating donor kidneys are considered marginal and the effect of mannitol and paracetamol drug intoxication will induce reversible sub-lethal injury. A period of dialysis is inevitable in clearing the reactive intermediates of mannitol and paracetamol. The kidneys behaved as traditional controlled NHBD at time of discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…It has been hypothesized that a locally produced metabolite induces proximal tubular cell necrosis while functional renal effects may also contribute (33,35,36). Our findings support the reversibility of acetaminophen‐induced nephrotoxicity (37,38).…”
Section: Discussionsupporting
confidence: 83%
“…It has been hypothesized that a locally produced metabolite induces proximal tubular cell necrosis while functional renal effects may also contribute (33,35,36). Our findings support the reversibility of acetaminophen‐induced nephrotoxicity (37,38).…”
Section: Discussionsupporting
confidence: 83%
“…However, according to 2015 data from 28 states with high-quality reporting, 63% of overdose deaths involved opioids (2). Moreover, use of organs for transplant after death due to other types of chemical poisoning is rare (43, 44). We could not determine the specific behavior for which ODDs were labeled as IRDs, and behaviors may differ between TDDs and MDDs who are labeled as IRDs.…”
Section: Discussionmentioning
confidence: 99%
“…MP may reduce the DGF of grafts retrieved from heart-beating donors and donation after cardiac death (DCD) donors by 20% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Many authors have reported on the beneficial effects of MP on organs from marginal and DCD donors (33)(34)(35)(36)(37). Reports on renal allograft function in relation to preservation mode have focused on observations up to 12 months post-transplant (38)(39)(40)(41)(42) or have applied statistical simulation based on the relationship between function and graft survival and DGF (43)(44)(45)(46)(47) or the relationship between DGF and acute rejection (48).…”
Section: Discussionmentioning
confidence: 99%